2011
DOI: 10.1164/rccm.201004-0666oc
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Emphysema Predicts Low Bone Mineral Density in a Tobacco-exposed Cohort

Abstract: Rationale: Studies demonstrating an association between chronic obstructive pulmonary disease and low bone mineral density (BMD) implicate factors distinct from treatments and severity of lung disease in the pathogenesis of osteoporosis. Whereas emphysema has been independently associated with vascular disease and other comorbidities, its association with BMD has not been well studied. Objectives: We explored the associations of BMD with computed tomography (CT) measures of emphysema and other risk factors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 51 publications
6
131
1
2
Order By: Relevance
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…the prevalence of reduced bone density and vertebral fractures in patients with chronic obstructive pulmonary disease (COPD) is high [1][2][3][4]; furthermore case-control studies have confirmed reduced bone mineral density (BMD) in COPD patients compared with controls [5][6], even in those with milder disease [7] while in patients who have osteoporosis and spinal deformities, reduced pulmonary function is related to the severity of osteoporosis [9][10][11] in the same way that the worse the level of lung function in COPD patients, the greater the likelihood of low BMD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, systemic inflammation, the use of systemic corticosteroids and the high prevalence of vitamin D deficiency, which are frequently observed in more severe stages of COPD, unequivocally contribute to a further loss of bone and muscle mass [43,45]. Observational studies also suggest that emphysema represents a particular phenotype that is associated with musculoskeletal impairment but the underlying mechanisms remain unclear [46][47][48]. Bone tissue is continuously renewed throughout life.…”
Section: Bone Mineral Density Lossmentioning
confidence: 99%
“…Heparinized peripheral blood was obtained from consecutive patients with IPF (5,14,16,37), healthy volunteers, and subjects with cigarette smoking-attributable chronic obstructive pulmonary disease (COPD) and/or emphysema (henceforth collectively denoted as COPD) (38,39).…”
Section: Subjects and Specimensmentioning
confidence: 99%
“…IPF acute exacerbations were defined by worsening hypoxemia and/or dyspnea during the preceding 30 days or less, with characteristic acute radiographic abnormalities, and no other attributable cause after thorough clinical evaluations (40). COPD was diagnosed by spirometry (38), and emphysema was detected and quantified by chest computed tomography scans (39). Subjects who were taking more than 10 mg prednisone per day, or other systemic immunosuppressants, were excluded from these analyses to avoid confounding effects of these medications on CXCL13 production (34).…”
Section: Subjects and Specimensmentioning
confidence: 99%